Lixiviación de nitrógeno en el cultivo de maíz en la época lluviosa. - Velásquez Mendoza, Carlos Geovanny (2016)
Nitrogen losses by leaching have been shown in several studies, which have shown that when this rate is high, the culture can not assimilate and take advantage of all the nitrogen provided by the fertilizations. Considering the above was conducted this investigation in order to assess the leaching of nitrogen in the cultivation of corn in the rainy season, for which a maize crop in the experimental farm "La Maria" was established, owned UTEQ , located at kilometer 7.5 of the road Quevedo - Mocache. The trial was conducted under a complete block design with seven treatments randomized in three replicates using the Tukey test at 95% for the comparison of means. The treatments consisted of applications at 15 and 45 days doing different subdivisions of applied nitrogen, the same as were: T1: 100-0 N, T2: 80-20 N, T3: 60 - 40 N, T4: 40 - 60 N, T5: 20-80 N, T6: 0 - 100 N, T7: 0 - 0 N (Witness). The main results it was observed that the amount of nitrogen absorbed by the crop was higher by applying the 40% requirement at 15 days of age and the remaining 45 days after planting 60%, surpassing 40.3 Kg/Ha the implementation of all the requirements at 15 days of age. The total nitrogen at the end of the culture was higher when all the nitrogen at 45 days old culture was applied to 42.7 Kg/Ha, with a result that the nitrogen remaining in the soil was not fully absorbed and held on the floor. Plant height 45 days old crop was not influenced by the treatments studied, posting averages between 126.7 and 153.3 cm. When the culture reached 100 days of age, differences were observed between the treatments where the application of all nitrogen requirement at 15 days exceeded 20.0 cm to the application of 20% at 15 days and 80% remaining 45 days. The application of total nitrogen in one application 15 days produced cobs larger diameter, length and weight, with 4.9 cm, 15.9 cm and 201.8 g, outperforming other treatments. By applying all the nitrogen requirement at 15 days old crop, higher performance was obtained, reflecting difference between 2239.9 and 4565.5 Kg/Ha over other treatments.